Protective Effect of Tang Wang One Decoction on the Retinal Vessels of Diabetic Rats. (6th March 2017) - Kou, Xinyun; Yang, Shufei; Qin, Yali; Yang, Chao; Deng, Tingting; Luo, Dan; Jin, Ming
Abstract : Objective . This study aimed to determine the influence of Tang Wang One Decoction (TWOD) on the retinal vessels of diabetic rats. Methods . The hemorheology of diabetic rats was observed. Morphological studies of retinal vessels were conducted using optical microscopy and electron microscopy. Immunological histochemistry assay was used to measure the expression levels of MMP-9, occludin, and claudin-5. Results . Obvious pathological damage was observed in the retinal vessels of diabetic rats. TWOD positively affected the hemorheology and morphology of retinal vessels. The decoction also decreased the expression of MMP-9 and increased the expression of occludin and claudin-5. Conclusions . The results suggest that the retinal protective effects of TWOD might be related to downregulation of MMP-9 and upregulation of occludin and claudin-5.